Pheochromocytoma-induced congestive heart failure and hypertension in a 21-year-old man-a Case Report - Chen, Shuoxian; Chen, Yufeng; Chen, Pingan (Journal of the Pakistan Medical Association, 2024)
Pheochromocytoma is a rare catecholamine-secreting mass which can lead to life-threatening cardiovascular complications and should be resected if confirmed. A 21-year-old male without any history of hypertension presented with congestive heart failure (HF) caused by pheochromocytoma-related cardiomyopathy; he was discovered to have hypertension at follow-up. A well-defined and uniform density mass was observed in his right adrenal region and confirmed to be pheochromocytoma. When the dilated left ventricle had become absolutely normal in size and hypertension was well controlled by medications, the patient needed no antihypertensive therapy at all after laparoscopic adrenalectomy at follow-up. Pheochromocytoma should be considered if HF occurred in patients, including young patients, with left ventricular enlargement and unknown medical history who initially presented with normal blood pressure. Even if the dilated left ventricle was restored and hypertension confirmed at follow-up, it could be well controlled by medications. Keywords: Pheochromocytoma, Heart failure, Hypertension.